Self-similarity in the structure of coarsened nanoporous gold - Jeon, Hansol; Kang, Na-Ri; Gwak, Eun-Ji; Jang, Jae-il; Han, Heung Nam; Hwang, Jun Yeon; Lee, Sukbin; Kim, Ju-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Nanoporous gold (np-Au) samples of ligament sizes 68.6, 248.6, 462.9, and 710.9 nm are prepared by heat treatment, and representative volumes are reconstructed by focused ion beam (FIB) tomography. The increase in relative density by thermal coarsening is not pronounced. We analyze the distribution of ligament size, surface-to volume ratio, and scaled connectivity density for coarsened np-Au, revealing that np-Au coarsens in a self-similar way. The measured activation energy for thermal coarsening supports that it is accomplished by surface diffusion of Au. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-BEHAVIOR; SCALING RELATIONS; YIELD STRENGTH; EVOLUTION; QUANTIFICATION; CONNECTIVITY; MORPHOLOGY; DIFFUSION; BONE; AU